Social and environmental determinants, household food insecurity - Graça, Pedro (2016)
Food security is defined as a situation that exists when “all people, at all times, have physical and economic access to sufficient, safe and nutritious food to maintain a healthy and active life. It is a multilevel concept, which includes four main dimensions: availability related to food supply; accessibility in order to ensure the physical and economic access to food; adequacy to meet nutritional needs in quantity and quality while respecting individual food preferences and cultural issues (utilization); and, lastly, stability of the guarantee of food security over time. According to the food security definition, it is abroad concept where all these dimensions are largely affected by a considerable number of factors related to: public policies of different sectors, food production/industry/distribution food systems, marketing and advertising of food, social support networks and individual determinants related to food choice behaviour.